Enhancing Cancer Immunotherapy Response Prediction using Multi-omics Integration and Deep Learning - Raja Kumar, Jambi Ratna; Dhabliya, Dharmesh; Dhablia, Anishkumar (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Cancer immunotherapy has emerged as a promising approach to treat various malignancies by harnessing the patient’s immune system to target cancer cells. However, the success of immunotherapy varies significantly among patients due to the complex and heterogeneous nature of the tumor microenvironment. To address this challenge, a novel machine learning approach is proposed to predict the response to cancer immunotherapy, utilizing a combination of multi-omics data integration and deep learning techniques.